Health Care and Government Policy - Laurinda Abreu (Publicações do Cidehus, 2019)
Government policy refers primarily to the actions planned and implemented by the executive branch of a state to meet its society's needs. One of the most demanding areas both for policy makers and in terms of people's expectations is health, which social analysts and historians place among the most dynamic sectors over the last century. This is the focus of this book. It includes examinations of two of the most pressing issues facing national healthcare services today - 'Health systems at the stage of complexity: the need for collaborative intelligence' by Constantino Sakellarides et al. and 'Longer and better lives: the European fountain of youth' by Patrice Bourdelais - alongside historical analyses covering both earlier periods - 'Not just one countryside: life chances in pre-industrial Sweden' by Jan Sundin and 'Health care and poor relief in Portugal: an historical perspective' by Laurinda Abreu - and more recent times - 'The roots of the health reform in Spain' by Enrique Perdiguero-Gil e Josep M. Comelles. As the authors in this volume show in detail, population growth and increased quality of life have been among the greatest achievements of the second half of the twentieth century, but they should not be taken for granted. The fragility of these gains has been demonstrated statistically. The state has to invest in the public policies that best protect its citizens, particularly at times of low economic growth such as we are now experiencing, and take preventive action to preclude major social and economic costs. Civil society plays no less important a role in protecting the greater good of social cohesion. In short, both state and civil society need to consider future health policy in such a way as to overcome the inefficiencies of the past and make full use of the opportunities offered by science and technology to improve people's quality of life.